2014
DOI: 10.5194/bg-11-6739-2014
|View full text |Cite
|
Sign up to set email alerts
|

Microbial food web dynamics during spring phytoplankton blooms in the naturally iron-fertilized Kerguelen area (Southern Ocean)

Abstract: Abstract. Microbial food web dynamics were determined during the onset of several spring phytoplankton blooms induced by natural iron fertilization off Kerguelen Island in the Southern Ocean (KEOPS2). The abundances of heterotrophic bacteria and heterotrophic nanoflagellates, bacterial heterotrophic production, bacterial respiration, and bacterial growth efficiency, were consistently higher in surface waters of the iron-fertilized sites than at the reference site in HNLC (high nutrient low chlorophyll) waters.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 58 publications
13
73
0
Order By: Relevance
“…Maiti et al (2013) demonstrated an inverse relationship between primary production and export efficiency in the Southern Ocean, contrasting with the positive relationship between primary production and export prevailing in most of the global ocean (Laws et al, 2011). These so called high biomass, low export regimes (HBLE, Lam and Bishop, 2007;Lam et al, 2011) appear to be characterized by enhanced heterotrophic microbial activity Christaki et al, 2014) and intense reprocessing and fragmentation of particulate matter by zooplankton. On the Kerguelen Plateau for example, net community production (NCP) was estimated to be 6.6 mol m À 2 yr À 1 (Jouandet et al, 2008), although only a small fraction of this NCP was exported out of the mixed layer (Rembauville et al, 2015b).…”
Section: Introductionmentioning
confidence: 94%
“…Maiti et al (2013) demonstrated an inverse relationship between primary production and export efficiency in the Southern Ocean, contrasting with the positive relationship between primary production and export prevailing in most of the global ocean (Laws et al, 2011). These so called high biomass, low export regimes (HBLE, Lam and Bishop, 2007;Lam et al, 2011) appear to be characterized by enhanced heterotrophic microbial activity Christaki et al, 2014) and intense reprocessing and fragmentation of particulate matter by zooplankton. On the Kerguelen Plateau for example, net community production (NCP) was estimated to be 6.6 mol m À 2 yr À 1 (Jouandet et al, 2008), although only a small fraction of this NCP was exported out of the mixed layer (Rembauville et al, 2015b).…”
Section: Introductionmentioning
confidence: 94%
“…Despite the much higher primary production for the fertilized area in comparison with the HNLC area, the export of organic matter remains relatively small during spring and summer . Low export efficiency suggests that the products of primary production are mainly recycled within the mixed layer by an efficient microbial loop (Sarthou et al, 2008;Obernosterer et al, 2008;Christaki et al, 2014;Malits et al, 2014). The carbon sequestration efficiency induced by iron fertilization remains proportionally relatively low (Jacquet et al, , 2015.…”
Section: High Primary Production In Naturally Iron-fertilized Bloomsmentioning
confidence: 99%
“…In early February (KEOPS 1), primary production and growth rate rapidly decreased in the euphotic layer from about 14 down to 2 µmol C L −1 d −1 and from ∼ 0.3 down to 0.01 d −1 respectively. Associated with these changes, the mixed layer production system evolved from being autotrophic, characteristic for spring, to heterotrophic with respiration exceeding photosynthesis Christaki et al, 2014). With nitrate and phosphate at non-limiting concentrations, a top-down control of phytoplankton development (mostly diatoms; Georges et al, 2014;Sackett et al, 2014) is the most likely cause of this change during the decay of the bloom in late summer (KEOPS 1; Carlotti et al, 2008;Brussaard et al, 2008;Sarthou et al, 2008).…”
Section: High Primary Production In Naturally Iron-fertilized Bloomsmentioning
confidence: 99%
“…During KEOPS 2 the incorporation of 3 Hleucine was used to estimate bacterial production. BP data are described in Christaki et al (2014). In Fig.…”
Section: Mesopelagic Ba Xs and Bacterial Productionmentioning
confidence: 99%
“…The same area was visited earlier in 2005 during summer at a late stage of the bloom (KEOPS 1; January-February 2005), offering a unique opportunity to estimate the main carbon fluxes over most of the growth sea- son. Mesopelagic C remineralization estimates are compared to particle and biological parameters as reported in other papers included in this issue Christaki et al, 2014;Dehairs et al, 2014;Laurenceau-Cornec et al, 2015;Planchon et al, 2014;van der Merve et al, 2015) and in Blain et al (2007), Christaki et al (2008), Jacquet et al (2008a), Park et al (2008) and Savoye et al (2008).…”
Section: Introductionmentioning
confidence: 99%